2013
DOI: 10.3917/rdm.041.0093
|View full text |Cite
|
Sign up to set email alerts
|

Faut-il intéresser les médecins pour les motiver ? Une analyse critique du paiement à la performance médicale

Abstract: Distribution électronique Cairn.info pour La Découverte. © La Découverte. Tous droits réservés pour tous pays.La reproduction ou représentation de cet article, notamment par photocopie, n'est autorisée que dans les limites des conditions générales d'utilisation du site ou, le cas échéant, des conditions générales de la licence souscrite par votre établissement. Toute autre reproduction ou représentation, en tout ou partie, sous quelque forme et de quelque manière que ce soit, est interdite sauf accord préalabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 14 publications
0
2
0
1
Order By: Relevance
“…According to them, there was a risk that cost savings would take precedence over patient needs and that patient autonomy would be compromised by directing medical decisions toward meeting indicator targets. Indeed, some studies have found that payment incentive models risk eroding professional norms by encouraging extrinsic over intrinsic motivation (Da Silva 2013). However, by 2015, GPs were generally in favour of this pay-for-performance model, with 95% declaring that they had modified their practice.…”
Section: Perception Of Physiciansmentioning
confidence: 99%
“…According to them, there was a risk that cost savings would take precedence over patient needs and that patient autonomy would be compromised by directing medical decisions toward meeting indicator targets. Indeed, some studies have found that payment incentive models risk eroding professional norms by encouraging extrinsic over intrinsic motivation (Da Silva 2013). However, by 2015, GPs were generally in favour of this pay-for-performance model, with 95% declaring that they had modified their practice.…”
Section: Perception Of Physiciansmentioning
confidence: 99%
“…Pay-for-performance arrangements are still lacking and current performance indicators, such as hospital readmission rates and length of stay, are imperfect (Degos, 2013; Or, 2014). When they do exist, for instance, for general practitioners, they reveal ambiguous outcomes (Da Silva, 2012, 2013; GAO and Social Affairs Committee, French Senate, 2014). Another, group of stakeholders, for example, private care providers took advantage of the NPM pro-competitive regulations to expand.…”
Section: Reforms and The Medical Professionmentioning
confidence: 99%
“…Dès 2009, le Contrat d'Amélioration des Pratiques Individuelles (CAPI) proposait aux médecins libéraux volontaires d'être payés à la performance en fonction de l'atteinte d'objectifs relatifs à la qualité des soins et à la prescription de médicaments génériques [8]. La convention médicale nationale de 2011 a systématisé l'usage de ce type de rémunération à travers la Rémunération sur Objectif de Santé Publique (ROSP) S'il est légitime pour l'assurance maladie de vouloir améliorer l'usage des ressources financières et de promouvoir la qualité des soins, la pertinence des dispositifs P4P mis en place à l'étranger a fait l'objet de nombreuses critiques [9,10,11,12]. Au-delà de la faible efficacité des dispositifs de P4P, la littérature internationale a aussi mis en évidence la possibilité que le P4P médicale produise des effets inattendus et négatifs sur la qualité et l'accès aux soins.…”
Section: Introductionunclassified